Empowerment Of Fish Cultivation Group By Using Embroidery Through Media And Thermal Marketing Post-Market Strategy - Kariyoto Kariyoto (Journal of Innovation and Applied Technology, 2018)
Catfish farming of today's era has a very lucrative and promising prospect, because of its nutritious and delicious flavors. The catfish beside it tastes delicious, the nutrient content is very high and good for the growth and health, so it is preferred by the wide circle of society, especially the Indonesian Nation. Catfish have advantages and advantages compared to other animal products are rich in Leusin and Lisin. Leucine (C6H13NO2) is an essential amino acid present in catfish, indispensable for the growth of children and maintaining nitrogen balance. Leucine is useful for the growth and formation of muscle proteins.